Science learning in early years: Effects of the Chinese television series Big Bird Looks at the World. Issue 2 (June 2017) - Hsueh, Yeh; Zhou, Zongkui; Su, Guimin; Lee, June; Kitzmann, Katherine
Big Bird Looks at the World, a Chinese co-production with Sesame Workshop, the producer of Sesame Street, uses science as a vehicle to promote curiosity, observation, and hands-on investigation among 3- to 7-year-old children. This study assessed the educational impact of Big Bird Looks at the World in a sample of 1860 children. Preschool and Grade 1–2 classrooms in Central and Southwestern China were randomized within schools to the experimental group (watched 42 11-minute episodes of Big Bird Looks at the World over a 7-week period) or the control group (engaged in normal class activities). Children's Big Bird Looks at the World content knowledge, in terms of science vocabulary and science facts, was assessed through interviews at baseline and post-test; children's responses were coded for quantitative analyses. Consistent with our assumptions based on cultural script theory, relatively brief exposure to Big Bird Looks at the World had significant benefits. Rural and urban children, children in preschool (ages 3–5) and Grades 1–2 (ages 6–7), and boys and girls all gained equally from exposure to the show. The results suggest that entertaining educational television has great potential for helping Chinese young children expand their science learning experiences.